Hukum Pernikahan dalam Masa Kehamilan di Indonesia (Studi Komparatif Hukum Islam dan Hukum Positif) - Ilham, Muhammad; Iskandar, Iskandar; Yusuf Qardlawi, Muhammad (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2026)
Abstracts: This study aims to analyze marriage during pregnancy through a comparative study between Islamic law and positive law in Indonesia. This research is a normative legal study employing statutory and conceptual approaches, analyzed qualitatively. The legal sources used include legislation, the Compilation of Islamic Law (KHI), fiqh literature, and relevant scholarly works. The findings show that Islamic law contains diverse views regarding the validity of marriage involving a woman pregnant as a result of zina. The Maliki and Hanbali schools tend to prohibit or restrict such marriage before certain requirements are fulfilled, such as a waiting period, childbirth, and repentance, whereas the Hanafi and Shafi’i schools generally permit it with differences concerning conjugal relations. Meanwhile, Indonesian positive law through Article 53 of the Compilation of Islamic Law allows a pregnant unmarried woman to marry the man who impregnated her without waiting for the child’s birth and without requiring a remarriage after delivery. This study concludes that there is a point of convergence between Islamic law and positive law in providing legal space for marriage during pregnancy, although they differ in terms of requirements, legal reasoning, and regulatory orientation. In Indonesian practice, the provisions of the KHI are more dominantly applied as an administrative legal basis, while fiqh perspectives, particularly the Shafi’i school, continue to influence legal understanding in order to realize public benefit and legal certainty for women and children.Keywords: Marriage During Pregnancy, Islamic Law, Positive Law, Compilation of Islamic Law, Family Law. Abstrak: Penelitian ini bertujuan menganalisis pernikahan dalam masa kehamilan melalui studi komparatif antara hukum Islam dan hukum positif di Indonesia. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual, yang dianalisis secara kualitatif. Sumber hukum yang digunakan meliputi peraturan perundang-undangan, Kompilasi Hukum Islam (KHI), literatur fikih, dan karya ilmiah yang relevan. Hasil penelitian menunjukkan bahwa hukum Islam memiliki keragaman pandangan mengenai keabsahan pernikahan perempuan hamil akibat zina. Mazhab Maliki dan Hanbali cenderung melarang atau membatasi pernikahan sebelum terpenuhinya syarat tertentu, seperti masa tunggu, melahirkan, dan taubat, sedangkan Mazhab Hanafi dan Syafi’i pada dasarnya membolehkan dengan perbedaan syarat dalam hubungan suami istri. Sementara itu, hukum positif di Indonesia melalui Pasal 53 KHI memperbolehkan perempuan hamil di luar nikah dinikahkan dengan laki-laki yang menghamilinya tanpa harus menunggu kelahiran anak dan tanpa akad ulang setelah anak lahir. Penelitian ini menyimpulkan bahwa terdapat titik temu antara hukum Islam dan hukum positif dalam memberikan ruang bagi pernikahan dalam masa kehamilan, meskipun keduanya berbeda dalam syarat, dasar pertimbangan, dan orientasi hukumnya. Dalam praktik di Indonesia, ketentuan KHI lebih dominan digunakan sebagai dasar administratif, namun tetap dipengaruhi oleh pandangan fikih, khususnya Mazhab Syafi’i, demi mewujudkan kemaslahatan dan kepastian hukum bagi perempuan dan anak.Kata kunci: Pernikahan dalam Masa Kehamilan, Hukum Islam, Hukum Positif, Kompilasi Hukum Islam, Hukum Keluarga